EFFECT OF COOPERATIVE LEARNING MODEL TYPE TEAM GAME TOURNAMENT (TGT) ON CROSS-CULTURAL SKILLS IN LEARNING SCIENCE SOCIAL KNOWLEDGE IN PRIMARY SCHOOL - Galih Dani Septiyan Rahayu; Febby Fajar Nugraha (PrimaryEdu : Journal of Primary Education, 2018)
The purpose of this research is to know the influence of cooperative model of game tournment team (TGT) type to cross cultural skill in IPS learning in fourth grade of SD Negeri Talaga kulon I. The method used in this research is pre experiment with one group pretest-posttest research design with instrument is a checklist observation system guidance. The result of this research is TGT type co-operative model have an effect on the improvement of cross cultural skills of elementary school students of Talaga Kulon I. This is seen from the comparison of pretest and posttest score and statistical test showing improvement especially on indicators "Harnessing social and cultural differences to work together effectively".